Effects of carbamazepine on dopamine- and serotonin-mediated neuroendocrine responses. - Elphick, M; Yang, J; Cowen, P (1990)
Neuroendocrine testing was carried out in seven male volunteers before and at the end of a 10-day course of carbamazepine (up to 700 mg daily). After carbamazepine treatment, the prolactin response to intravenous administration of the serotonin precursor tryptophan (5 g) was significantly enhanced, but there was no change in basal plasma tryptophan level or in tryptophan disposition after infusion. The prolactin response to intravenous protirelin (6.25 micrograms) was unaltered. Carbamazepine treatment also produced an increase in the growth hormone response to subcutaneous administration of the dopamine agonist apomorphine hydrochloride (5 micrograms/kg). These data suggest that carbamazepine may alter brain serotonin and dopamine function in humans. Such effects could be involved in the therapeutic properties of carbamazepine in affective disorder.